Using Different Feed Additives as Alternative to Antibiotic Growth Promoter to Improve Growth Performance and Carcass Traits of Broilers - Hassan, H.M.A.; Samy, A.; Youssef, Amani W.; Mohamed , M.A. (International Journal of Poultry Science, 2018)
Background and Objective: Several feed additives have been used to improve feed efficiency and growth performance of broiler. This growth experiment aimed to study the effect of using different feed additives compared to Bacitracin Methylene Disalicylate antibiotic growth promoter on growth performance and carcass traits. Methodology: Three hundred broiler chicks were divided into six treatment groups (5 replicates, 10 birds each treatment). A basal corn-soybean meal diet was formulated. Treatment 1 was basal diet without additives (as a control group); treatments 2, 3, 4, 5 and 6 were the control diet supplemented with 0.025% Bacitracin Methylene Disalicylate (antibiotic), 0.05% Saltose (probiotic), 0.05% Clostat (probiotic), 0.05% Clostri-stop (probiotic) or 0.1% Sangrovit (phytobiotic), respectively. Results: The results showed that supplementation of different feed additives or antibiotic significantly (p<0.001) improved body weight gain (BWG) and feed conversion ratio (FCR) in the finisher period (from 26-35 days of age) and the overall period (1-35 days) compared with the control (without additives). Results of carcass traits showed that there was a significant (p<0.05) increase in carcass weight and dressing percentage of broilers fed antibiotic or feed additives supplemented diets compared to those fed the control diet. However, internal organs were not affected by supplementation. Conclusion: Using probiotics or phytobiotics in broiler diet as feed additives appeared to be superior compared to antibiotic growth promoter. It could be concluded that, addition of feed additives containing Bacillus sp., Clostridium butyricum (probiotics) or Sanguinarine (phytobiotics) to broiler diets could significantly improve growth performance and carcass traits more efficiently and safely than antibiotic growth promoter. These could be good alternatives to antibiotic growth promoters in broiler diets.